Peran Teknologi dan Inovasi dalam Mendukung Keberhasilan Transformasi Digital di Indonesia - Endah Arum Wangi (Lembaga Yasin AlSys, 2026)
Digital transformation in Indonesia still faces challenges related to gaps in digital infrastructure, technological readiness, and innovation capacity that has not yet been optimized. This study aims to analyze the role of technology and innovation in supporting the success of digital transformation and its impact on economic growth and community welfare. This study used the Systematic Literature Review (SLR) method with the PRISMA approach, through an analysis of 22 selected articles from 66 publications during the 2020–2024 period. The results show that technology serves as a key enabler in improving operational efficiency, accelerating cross-sector digitalization, and strengthening the competitiveness of MSMEs. Innovation, particularly in business models and digital-based public services, contributes to increasing economic inclusivity and service quality. However, digital transformation still faces obstacles in the form of infrastructure inequality, low digital literacy, and resistance to change. The conclusion of the study emphasizes that the success of digital transformation in Indonesia is strongly influenced by the synergy between the use of technology and sustainable innovation. The implications of this study emphasize the importance of inclusive digital infrastructure development policies, improving public digital literacy, and adaptive innovation strategies by industry actors to promote sustainable and competitive digital economic growth.